Não cumulatividade do PIS e da COFINS - Araújo, Larissa Cavalcante Teixeira (2018)
The objective of the present study is to analyze the non-cumulativity disposed in the legal framework for the contribution to PIS and COFINS. In order to do so, it was firstly necessary to present the materiality of these social contributions (revenue and billing). After, we explain the techniques of collection of taxes on sales. Next, we face the question of being the noncumulative principle or rule, bringing, also, its meaning extracted from the constitutional text. Once these considerations have been made, we will detail the non-cumulative structure regarding the contribution to PIS and COFINS specifically, discussing the method chosen by the legislator to operationalize it, the expected credit discount system, among other points. Finally, we examine how the ordinary legislator addressed the application of this noncumulative system, highlighting the hypotheses of expected credits, as well as their fences